Tests to evaluate the ecological impact of treated ballast water on three Chinese marine species - 张亚楠 王子羲 蔡磊明 蔡翔 孙文俊 马立青 (Chinese journal of oceanology and limnology, 2014)
Ballast water has been a topic of concern for some time because of its potential to introduce invasive species to new habitats. To comply with the International Convention for the Control and Management of Ships＇ Ballast Water and Sediments, members of the International Maritime Organization （IMO） must equip their ships with on-board treatment systems to eliminate organism release with ballast water. There are many challenges associated with the implementation of this IMO guideline, one of which is the selection of species for testing the ecological impacts of the treated ballast water. In the United States, ballast water toxicity test methods have been defined by the United States Environmental Protection Agency. However, the test methods had not been finalized in China until the toxicity test methods for ballast water were established in 2008. The Chinese methods have been based on species from three trophic levels： Skeletonema costatum, Neomysis awatschensis, and Ctenogobius gymnauchen. All three species live in broad estuarine and open sea areas of China; they are sensitive to reference toxicants and acclimatize easily to different conditions. In this paper, the biological characteristics, test processes and statistical analysis methods are presented for the three species. Results indicate that the methods for evaluating these three organisms can be included in the ecological toxicity tests for treated ballast water in China.